Bibliometry of slow tourism through the software lens of VOSviewer and MS Excel - Ngoc Thu Vu; Hong Long Pham; Samuel Tietse (Via@)
The concept of "slow tourism" has emerged from the active involvement of tourists, destination management organisations, and associated service providers, establishing itself today as an alternative to mass tourism. This study proposes a quantitative analysis of the scientific production on the subject, based on Scopus data and using a corpus of 120 documents (articles, conference proceedings, book chapters, books). Through the use of VOSviewer and MS Excel, combining several analytical methods (co-citations, keyword co-occurrences, bibliographic coupling), we obtained a detailed overview of the current state of research. The results confirm that the field of slow tourism remains emerging and fragmented, structured around distinct thematic poles. The bibliometric analysis provides an original perspective, despite limitations linked to algorithmic biases and the exclusive use of the Scopus database. Future research could cross-reference multiple sources and methods to refine these initial findings.